Anugerah Dibalik Sebuah Wabah - , LISTER EVA SIMANGUNSONG; , Prof. Dr. Bambang Purwanto, M.A. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This study discusses about the social history of communities in Tanah Karo when the epidemic of leprosy struck in the late 18th century. This topic is chosen because there are not many studies about the study of social history in Tanah Karo society, especially in the aspects of a disease outbreak. The issue in this study is the influence of the epidemic of leprosy control efforts towards social change society in Tanah Karo, 1906-1930's. To answer the point, this study uses the methods of history (historical method) by using three stages, heuristics, source criticism and interpretation (explanation). Written sources are used in the form of literature, archives, documents or secondary sources of books, journals, articles and magazines that obtained from the National Library and National Archives and Jakarta GBKP Karo of North Sumatra and Regional Library. Based on these results, it can be concluded, first, the society's negative attitudes towards the social environment and the natural environment has caused an outbreak of leprosy is endemic and affects people's economic decline and the emergence of new social problems. Second, the condition is then pushed the Colonial government to make efforts to overcome the system of \"separation and isolation\" of established settlements and Lau Simomo leprosy hospital in 1906. Third, prevention efforts have led to outbreaks of leprosy in the field of social change beliefs, education, economy, health as well as changes in the social field of the lepers in the settlement Lau Simomo and society in Tanah Karo, in other words there is no society in Tanah Karo untouched by the social changes resulting from efforts to control outbreaks of leprosy by the Colonial Government.